PRODIGY: AN INNOVATIVE APPROACH FOR CHARACTER DEVELOPMENT - Samsiah Mohd Jais; Ab. Aziz Md. Yatim; Mohammed Aziz Shah Mohammad Arip (LPPM Universitas Negeri Yogyakarta, 2012)
Abstract: The formation and development of healthy and effective characters among the students are closely related to the role played by a counselor at school. However, in the era of globalization, the role of counselor in the development of good character in students is more difficult and complicated. Thus, apart from the knowledge and skills, counselor should have an effective strategy in encouraging the development of good character in young children. The purpose of this paper is to introduce a ‘Prodigy’ as an approach to assist the guidance and counseling teachers as well as other individuals who play vital roles in the development and improvement of students’ behavior. Prodigy is unique and innovative because it helps counselors to understand the essential elements for the improvement and enhancement of human development in schools; and comprehensive as they integrate the affective, cognitive and behavioral components of character development. This paper discusses relevant course modules for character development and touches the benefits of using Prodigy in fostering character development.Keywords: Prodigy, counseling, character development, character counseling, counseling modules